KORELASI ANTARA KOORDINASI MATA-KAKI DENGAN KEMAMPUAN SEPAK SILA DALAM PERMAINAN SEPAK TAKRAW ATLET KLUB DONDONG MERAH TAHUN 2014 - Maimun Nusufi (Universitas Negeri Medan, 2016)
Abstract: “The study entlited “Correlation Of Persimmon Between-Eye Coordination Article Search Google Football Ability Sila In Games Sepak Takraw Athletes Dondong Club Red 2014”. Aiming for a review of relations know-eye coordination persimmon Againts football ability sila hearts Games Sepak Takraw athletes Dondong club Red 2014. Research respondents amounted to 15 orangutans. The data is processed using statistical techniques hearts with Forms calculation average value (Mean), standard deviation (SD) and test correlation. Results showed: There is a significant relationship between eye coordination-persimmon with soccer ability sila (r = 0.52). Correlation of 27 % (0.522 x 100%) Againts sila football ability. While the value t = 2,202 big more on degrees Freedom From tabel 15-2 (df = 13) in the level of significance of α = 0.05 is 1.771. That is 2,202> 1,771. Then Ho is rejected, meaning that relationship are significant persimmon between-eye coordination against football ability sila games Sepak Takraw athletes hearts club Red Dondong 2014.Keywords : Eye-Foot Coordination. Ability Football SilaAbstrak: Penelitian yang berjudul “Korelasi antara Koordinasi mata-kaki Dengan Kemampuan Sepak Sila Dalam Permainan Sepak Takraw Atlet Klub Dondong Merah Tahun 2014”. Bertujuan untuk mengetahui hubungan koordinasi mata-kaki terhadap kemampuan sepak sila dalam permainan Sepak Takraw atlet klub Dondong Merah tahun 2014. Responden penelitian berjumlah 15 orang. Hasil penelitian menunjukkan: terdapat hubungan yang signifikan antara koordinasi mata-kaki dengan kemampuan sepak sila (r = 0,52). Korelasi sebesar 27% (0,522 x 100%) terhadap kemampuan sepak sila. Sedangkan nilai thitung= 2,202 lebih besar dari ttabel pada derajat kebebasan 15-2 (dk =13) pada taraf signifikasi α = 0,05 adalah sebesar 1,771. Artinya 2,202 > 1,771. Maka Ho ditolak, artinya terdapat hubungan yang signifikan antara koordinasi mata-kaki terhadap kemampuan sepak sila dalam permainan Sepak Takraw atlet klub Dondong Merah Tahun 2014.Kata kunci : koordinasi mata-kaki, kemampuan sepak sila